2022
DOI: 10.3390/ijerph191711061
|View full text |Cite
|
Sign up to set email alerts
|

Are You Willing to Protect the Health of Older People? Intergenerational Contact and Ageism as Predictors of Attitudes toward the COVID-19 Vaccination Passport

Abstract: Since the beginning of the COVID-19 pandemic, the vulnerability of older people to COVID-19 has been stressed in political discourse and the mass media, with the call to protect older adults. Therefore, policies aimed at reducing the spread of coronavirus, such as the COVID-19 vaccination passport policy, might be perceived as policies aimed at preserving the health of older people, and negative attitudes toward older people (i.e., ageism) might underlie negative attitudes toward such policies. While intergene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The insignificant moderation effect of contact quality contradicts previous studies conducted before the pandemic, which demonstrate the effect of contact quality on reducing ageism reduction (Bousfield and Hutchinson, 2010). These results may suggest that the COVID-19 pandemic has dramatically changed the frequency and quality of interpersonal contact (Visintin and Tasso, 2022). It is possible that the social-distancing policy and the fear of in-person interaction led to the insignificant effect of contact quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The insignificant moderation effect of contact quality contradicts previous studies conducted before the pandemic, which demonstrate the effect of contact quality on reducing ageism reduction (Bousfield and Hutchinson, 2010). These results may suggest that the COVID-19 pandemic has dramatically changed the frequency and quality of interpersonal contact (Visintin and Tasso, 2022). It is possible that the social-distancing policy and the fear of in-person interaction led to the insignificant effect of contact quality.…”
Section: Resultsmentioning
confidence: 99%
“…The insignificant moderation effect of contact quality contradicts previous studies conducted before the pandemic, which demonstrate the effect of contact quality on ageism reduction (Bousfield and Hutchinson, 2010). Due to infection containment measures, the COVID-19 pandemic has dramatically changed the frequency and quality of interpersonal contact (Visintin and Tasso, 2022) and may have long-term implications for workplace dynamics. This study serves as an initial inquiry in this area and encourages future research to investigate intergenerational workplace relationship in the post-pandemic era and the effects of contact frequency and quality as two major components of the intergenerational intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it may create intergenerational tension. As adherence to these measures might differ between adult children and their parents (Visintin & Tasso, 2022), expectations about support might not be in concordance as well. Greater stringency also prevents other sources of social contact and informal support (e.g.…”
Section: Effect Of Changes In Intergenerational Support On Depressive...mentioning
confidence: 99%
“…As highlighted by Visintin and Tasso [42], during the pandemic, media and political discourse suggested that people with debilitating diseases or older people had a higher likelihood of severe complications in case of COVID-19 infection. In Italy, the official communications during the early stages of the pandemic underlined that COVID-19 was more likely to severely affect only vulnerable people, specifically older adults, and sick people, leading to the diffusion of age-related rhetoric by Italian media about COVID vulnerability [43,44].…”
Section: Italian Young Adults' Psychological Well-being During the Pa...mentioning
confidence: 99%
“…Along with representing older people as the most vulnerable population [3], national media discourse misleadingly contributed to conveying that "only older adults, not the young" were an at-risk population for COVID-19 infection [43] (p. 535). Along this line, Sjölander-Lindqvist et al [45] found that, within the Italian context, the communication of then Prime Minister Conte aimed at underlining the importance of an intergenerational building of meaning around older people's deaths in Italy, encouraging Italians to adopt preventive behaviors and social distancing to protect "especially the health of our grandparents" [42] (p. 2).…”
Section: Italian Young Adults' Psychological Well-being During the Pa...mentioning
confidence: 99%